2020
DOI: 10.1186/s43141-020-00085-z
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on promising anti-viral therapeutic candidates identified against main protease from SARS-CoV-2 through various computational methods

Abstract: Background The COVID-19 pandemic caused by SARS-CoV-2 has shown an exponential trend of infected people across the planet. Crediting its virulent nature, it becomes imperative to identify potential therapeutic agents against the deadly virus. The 3-chymotrypsin-like protease (3CLpro) is a cysteine protease which causes the proteolysis of the replicase polyproteins to generate functional proteins, which is a crucial step for viral replication and infection. Computational methods have been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 88 publications
(90 reference statements)
0
42
0
Order By: Relevance
“…Notably, humans do not have a 3CL pro homologue. Thus, 3CL pro is an attractive target for COVID-19 antiviral drug development [ [16] , [17] , [18] ].
Figure 2 Schematic representation for the localization and function of possible inhibitor classes against 3CL pro from SARS-CoV-2 (Adopted from Singh et al [ 18 ]).
…”
Section: Sars-cov Chymotrypsin Like Protease (3cl Pro mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, humans do not have a 3CL pro homologue. Thus, 3CL pro is an attractive target for COVID-19 antiviral drug development [ [16] , [17] , [18] ].
Figure 2 Schematic representation for the localization and function of possible inhibitor classes against 3CL pro from SARS-CoV-2 (Adopted from Singh et al [ 18 ]).
…”
Section: Sars-cov Chymotrypsin Like Protease (3cl Pro mentioning
confidence: 99%
“… Schematic representation for the localization and function of possible inhibitor classes against 3CL pro from SARS-CoV-2 (Adopted from Singh et al [ 18 ]). …”
Section: Sars-cov Chymotrypsin Like Protease (3cl Pro mentioning
confidence: 99%
“…Based on analyses of structure characteristics of M pro and the free energy of binding between the active site and potential targeting compounds, in silico approaches including molecular docking can provide insights that lead to discovering new drug candidates or repurposing preexisting drugs. In silico studies suggested that many compounds exhibit inhibitory effects against M pro , and that these compounds include flavonoids, peptides, terpenes, quinolines, nucleoside or nucleotide analogues, conventional protease inhibitors, phenalene, antibiotic derivatives, imidazole, and indoles [26] . Biochemical high throughput screening (HTS) strategies have also been applied to screen synthetic or natural compounds.…”
Section: Genome Structure Of Sars-cov-2 and Key Drug Targetsmentioning
confidence: 99%
“…These values are lower than the binding energy obtained when we docked viomycin against the same amino acids, which stood at -3 kcal/mol. Viomycin is being actively pursued as a promising inhibitor of the SARS-CoV-2 main protease 25 , and the ability of the two Ocimum flavonoids to bind better to the critical active site amino acid residues of the main protease 21 holds promise for the two flavonoids to be checked more intensively. We docked the two flavonoids against the RNA-dependent RNA polymerase of the SARS-CoV-2 virus.…”
Section: A B C D E Fig 3: 2d Images Of the Interaction Of Vicenin-1 With The Selected Amino Acid Residues Of (A) Covid The Main Protease mentioning
confidence: 99%